The Fiqhi Rule “Spending by Order of the Judge is like Spending by Order of the Owner” and its Aapplications: A Legal Jurisprudence Study - Qudah, Zakaria Muhammad Faleh (Dirasat: Shari’a and Law Sciences, 2020)
The study clarified the meaning of the jurisprudential rule and the jurisprudential discipline, and the differences between them. The study focused on the jurisprudence rule, "Spending by order of the judge is like spending by order of the owner." The study clarified the origin of the rule and showed its jurisprudential rooting by explaining its evidence, explaining the meanings of its words, and clarifying its general meaning. The study showed the urgent need to apply this rule because of its importance in achieving people’s interests and meeting their necessary needs in their dealings, and cutting off the means of conflict and quarrels between spouses in the event of insolvency in paying the due alimony. The judge has general jurisdiction over funds to address such situations. The study mentioned a number of jurisprudential applications of this rule that came scattered in various chapters of jurisprudence books, with each of them directly appended to what is appropriate in the laws of the Hashemite Kingdom of Jordan, whether within the framework of civil law or personal status law. Then a number of applications of this rule were mentioned from real cases in which judgments were issued by the Jordanian Sharia courts (in the city of Irbid in particular).